Strengthening Community Involvement in Grant Review: Insights from the Community–University Research Partnership (CURES) Pilot Review Process. Issue 2 (23rd January 2014) - Paberzs, Adam; Piechowski, Patricia; Warrick, Debra; Grawi, Carolyn; Choate, Celeste; Sneed, Glenda; Carr, Diane; Lota, Kanchan; Key, Kent; Alexander, Valerie; Ghosh, Pratik; Sampselle, Carolyn
Abstract In 2007, the Michigan Institute for Clinical and Health Research (MICHR) at the University of Michigan received a Clinical and Translational Science Award (CTSA). Within MICHR, the Community Engagement (CE) program supports partnership efforts between researchers, practitioners, and community‐based organizations in specific focal communities throughout Michigan. A key component of the CE program is the Community Engagement Coordinating Council, a group that provides input and guidance on program priorities, strategic planning, and reviews pilot funding proposals for community–academic partnerships. This paper will describe a unique MICHR pilot funding mechanism for Community–University Research Partnerships (CURES) with an emphasis on the ways that community partners are involved in the review process, as well as the benefits, challenges, and insights gained over 5 years of pilot review. There is a growing need for community involvement and expertise in review of funding proposals for community‐engaged research at both institutional and federal levels. The CURES pilot review process is one example of an institutional effort to engage community partners in university funding decisions and has demonstrated clear benefit toward accomplishing the aims of the CTSA.